Social Entrepreneurs as Responsible Leaders: ‘Fundación Paraguaya’ and the Case of Martin Burt - Maak, Thomas (Journal of business ethics, 2012)
A country known for its longstanding struggle with corruption and dubious governments may not be the obvious venue for a socio-economic revolution that is expected to play an important role in the elimination of global poverty. However, Paraguay, an ‘island without shores’, as the writer Augusto Roa Bastos once described it, is home to one of the world’s most innovative social enterprises—the Fundación Paraguaya. While its achievements and success are the result of a team effort, its remarkable development can be largely attributed to Martín Burt, the founder and chief executive. We study the case of Fundación Paraguaya—the first and longest-running non-governmental organisation in Paraguay—with two primary research objectives: (1) to analyse the organisation’s pioneering way of solving social problems under difficult socioeconomic circumstances and its increasingly global outreach to eradicate poverty; (2) and to analyse the responsible leadership of Martín Burt.